Hereditary Breast and Ovarian Cancer Syndromes - Ghasemi Darestani, Nadia; Ghasemi Darestani, Ramin; Hshemi, Soheyla; Rahimi, Zahra; Janghorbanian Poodeh, Raheleh (Asian Pacific Journal of Environment and Cancer, 2024)
Women who inherit a mutation in the BRCA1 or BRCA2 gene are much more likely to develop breast and ovarian cancer. A woman’s specific risk depends on many factors including her age, whether she has a BRCA1 or BRCA2 mutation, and her medical and family history. Most women with breast or ovarian cancer have a sporadic cancer. The majority of women with inherited breast and/or ovarian cancers carry a pathogenic variant (ie, deleterious or harmful mutation) in breast cancer susceptibility gene 1 (BRCA1) or breast cancer susceptibility gene 2 (BRCA2), some hereditary breast cancers are due to other rare hereditary syndromes, such as Li-Fraumeni and Cowden syndromes, which are associated with pathogenic variants in the tumor protein p53 (TP53) and phosphatase and tensin homolog tumor suppressor (PTEN) genes, respectively. Pathogenic variants in other genes also confer a heightened risk of breast and/or ovarian cancer.hereditary breast and ovarian cancer syndromes associated with genes other than BRCA1/2.